Law Enforcement Policy by the Police in Combating Online Gambling in Indonesia: Kebijakan Penegakan Hukum Oleh Kepolisian Dalam Menanggulangi Judi Online di Indonesia - Tanuwijaya, Jhonathan; Hutabarat, Rugun Romaida (Indonesian Journal of Law and Economics Review, 2025)
General Background: The exponential growth of digital technology has accelerated the emergence of online gambling as one of the most pervasive forms of cybercrime in Indonesia, generating severe social, economic, and psychological repercussions. Specific Background: Despite the government’s introduction of Law No. 1 of 2024 amending the Electronic Information and Transactions Law, online gambling continues to proliferate, involving transnational networks and massive financial transactions. Knowledge Gap: Previous studies have insufficiently addressed the complex interaction between legal frameworks, enforcement capacity, and sociocultural factors that hinder the effectiveness of policing online gambling. Aims: This study aims to analyze the Indonesian National Police’s legal policies and enforcement strategies in combating online gambling, focusing on barriers such as digital evidence collection, jurisdictional limitations, and public legal awareness. Results: Findings reveal that punitive measures alone are ineffective, as enforcement faces constraints in tracking cross-border transactions, accessing banking data, and countering influencer-driven promotions. Novelty: This research integrates criminological, psychological, and legal perspectives to propose a multidimensional approach combining penal and non-penal measures. Implications: Strengthening legal literacy, enhancing digital forensics, and promoting international cooperation are essential to develop adaptive, preventive, and rehabilitative strategies for addressing online gambling in Indonesia. Highlights: Highlights the ineffectiveness of punitive measures in tackling transnational online gambling. Identifies major enforcement barriers: digital evidence, jurisdiction, and public awareness. Proposes integrative legal strategies combining penal action with education and rehabilitation. Keywords: Online Gambling, Law Enforcement, Police Policy, Cybercrime, Legal Reform